Program Bimbingan Berbasis Sirah Nabawiyah untuk Mengembangkan Karakter Positif Remaja - Hidayat, Ade; Rakhman, Alwi Bani; Nurchotimah, Aulia Sholichah Iman; Azizah, Nurul (Universitas Muhammadiyah Metro, 2024)
This research aims to build a practical and feasible guidance program for developing positive adolescent character. One approach to providing guidance is to use Sirah Nabawiyah learning materials, namely a pattern of guidance activities using meaning and contextualization of the life journey of the Prophet Muhammad, both before and after he was appointed a Prophet. This research contextualizes the Prophet Muhammad's teenage years. This research uses a quantitative approach and a quasi-experimental research design. This research shows that the average score of the experimental group who took part in Sirah Nabawiyah-based guidance is better than the average score of the control group who took conventional guidance/learning, so the conclusion obtained is that Sirah Nabawiyah-based guidance services are more effectively used to improve the positive character of adolescence. This Sirah Nabawiyah-based guidance program is recommended to be considered as one of the programs for carrying out learning and guidance activities, significantly improving positive character.